Academic activism on behalf of children during the COVID-19 pandemic in Israel; beyond public health advocacy - Ora Paltiel; Hagit Hochner; David Chinitz; A. Mark Clarfield; Alex Gileles-Hillel; Amnon Lahad; Orly Manor; Ran Nir-Paz; Ari Paltiel; Chen Stein-Zamir; Ekaterina Yazhemsky; Ronit Calderon-Margalit (BMC, 2021)
Abstract Among the challenges presented by the SARS-CoV2 pandemic are those related to balancing societal priorities with averting threats to population health. In this exceptional context a group of Israeli physicians and public health scholars (multidisciplinary academic group on children and coronavirus [MACC]) coalesced, examining the role of children in viral transmission and assessing the necessity and consequences of restricted in-class education. Combining critical appraisal and analytical skills with public health experience, MACC advocated for safe and monitored school re-opening, stressing the importance of education as a determinant of health, continuously weighing this stance against evolving COVID-19-risk data. MACC's activities included offering research-based advice to government agencies including Ministries of Health, Finance, and Education. In a setting where government bodies were faced with providing practical solutions to both decreasing disease transmission and maintaining society's vital activities, and various advisors presented decision-makers with disparate views, MACC contributed epidemiological, clinical and health policy expertise to the debate regarding school closure as a pandemic control measure, and adaptations required for safe re-opening. In this paper, we describe the evolution, activities, policy inputs and media profile of MACC, and discuss the role of academics in advocacy and activism in the midst of an unprecedented public health crisis. A general lesson learned is that academics, based on the rigor of their scientific work and their perceived objectivity, can and should be mobilized to pursue and promote policies based on shared societal values as well as empiric data, even when considerable uncertainty exists about the appropriate course of action. Mechanisms should be in place to open channels to multidisciplinary academic groups and bring their input to bear on decision-making.